Considerations regarding the Refusal of Execution of the European Arrest Warranty - Ioan Aron (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The third millennium comes up with a new framework in the field of social life, as well as in the field of cross-border crime, which faced significant increases, generated by the enlargement of the European Union, which eliminated internal border controls thus facilitating the movement of criminals and goods, which are the subject of organized crime and terrorism. The institution of extradition, in this context, experienced some operational imperfections, so that it was necessary to adopt new judicial procedures for the arrest and surrender of offenders in the Member States to the requesting State by establishing the European arrest warrant.